ANALISIS KEMAMPUAN LITERASI DIGITAL SISWA KELAS V SEKOLAH DASAR MITRA BATIK - Thendrawati, Cynthia; Nur, Lutfi; Muharram, Muhammad Rijal Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of digital literacy skills as a key competency in the 21st century for elementary school students. The main objective of this research was to analyze in depth the digital literacy profile of fifth-grade students at Mitra Batik Elementary School through four main dimensions proposed by Paul Gilster, namely: internet searching, hypertextual navigation, content evaluation, and knowledge assembly. The research employed a quantitative descriptive method with a total sample of 23 fifth-grade students. Data were collected through an instrument using a Likert scale. The results showed that, overall, the students’ digital literacy skills were categorized as “High.” The hypertextual navigation dimension obtained the highest percentage (91%), while internet searching scored 61%. These findings indicate that although students are highly proficient in technical navigation, intensive guidance is still needed in developing more effective information-searching strategies to support academic achievement.